Analysis and Evaluation of West Semarang Distribution Pipe Network System Municipal Waterworks in Semarang City - Bernadinus Gunawan Broto Miseno; Budi Prasetyo Samadikun; Anik Sarminingsih (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2022)
The need for clean water is related to the growth rate and population density. High population density affects access to clean water. The population in the DWSS (Drinking Water Supply System) area of West Semarang is concentrated in three sub-districts, namely West Semarang (148,879 people), Ngaliyan (141,727 people), and Tugu (32,822 people). With the average population growth rate of Semarang City from 2011 to 2020 of 0.89%, the need for clean water will continue to increase. The condition of clean water services in Semarang City, which Municipal Waterworks manage, needs to be improved, both in terms of coverage and continuity of service distribution. The research method used is the method of field research and literature. Hydraulic data retrieval was obtained through field observations and water usage data from the internal Municipal Waterworks in Semarang City. The data were analyzed using the epanet program. From the analysis results, there were areas with significant differences in water pressure values , and at peak hours, there were areas that did not get sufficient water supply. It can be concluded that there are problems in the piping network in the West Semarang DWSS area.